A budget for the ecological footprint of buildings is possible: A case study using the dwelling construction cost database of Andalusia. (November 2019) - Freire-Guerrero, Antonio; Alba-Rodríguez, M. Desirée; Marrero, Madelyn
Highlights: Generate budgets that calculate the economic-anvironmental cost is possible, incorporating EF indicator in its structure. All the basic elements contained in the ACCD (approx.7000). These elements are combined into work units employed in budgets. The economic control of the budgets allows to introduce the environmental impact by a common language existing in the sector. The model proposed is sensible to changes in the materials, machinery and workforce employed in the projects. Abstract: Over the last decade, the ARDITEC research group has developed a methodology for the calculation of the ecological footprint of buildings throughout their life cycle. The model starts with the evaluation of the information in the budget on whether they are urbanization, construction, renovation, or demolition projects, and evaluates its impact employing databases of Life Cycle Analysis. In the present work, the methodology is adapted in order to be valid in the determination of project budgets that simultaneously calculate the economic cost and its ecological footprint. The boundaries of the problem are the ones already defined in the Andalusian construction cost databases. The database has a pyramidal structure (basic elements or units) enables either the impact of work units to be combined or the cost or impact to be determined of different stages (earthworks, foundations, structures, etc.). The present work evaluates, for the first time, all the basic elements in dwelling construction, approximately 7000 items. Finally, a case study of the urbanization and construction of dwellings in Andalusia is presented. The economic control of the budgets provides the opportunity to introduce the control of the environmental impact by using a common language already in place in the sector.